2011
DOI: 10.3892/ijmm.2011.662
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glucosamine derivatives and uronic acids on the production of glycosaminoglycans by human synovial cells and chondrocytes

Abstract: Abstract. Glucosamine (GlcN) has been widely used to treat osteoarthritis (OA) in humans. However, its chondroprotective action on the joint is poorly understood. In this study, to elucidate the chondroprotective action of GlcN, we examined the effects of GlcN-derivatives (GlcN and N-acetyl-d-glucosamine) and uronic acids (d-glucuronic acid and d-galacturonic acid) (0.1-1 mM) on the production of glycosaminoglycans (GAG), such as hyaluronic acid (HA), keratan sulfate and sulfated GAG by human synovial cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
(17 reference statements)
1
5
0
1
Order By: Relevance
“…The same group compared glucosamine hydro-chloride to N-acetylglucosamine [22] and observed no effect of N-acetylglucosamine on HA production whereas glucosamine hydrochloride appeared to modulate this parameter. The same conclusion was reached in the study by Igarashi and colleagues [21]. In contrast, another study compared the effect of native glucosamine and N-acetylglucosamine on the metabolic activity of human articular chondrocytes [26].…”
Section: Update On In Vitro Datasupporting
confidence: 68%
See 2 more Smart Citations
“…The same group compared glucosamine hydro-chloride to N-acetylglucosamine [22] and observed no effect of N-acetylglucosamine on HA production whereas glucosamine hydrochloride appeared to modulate this parameter. The same conclusion was reached in the study by Igarashi and colleagues [21]. In contrast, another study compared the effect of native glucosamine and N-acetylglucosamine on the metabolic activity of human articular chondrocytes [26].…”
Section: Update On In Vitro Datasupporting
confidence: 68%
“…The pro-anabolic effects of glucosamine were demonstrated in both human chondrocytes and synovial cells, where glucosamine was shown to induce the production of hyaluronic acid (HA) and to directly enter the GAG biosynthetic pathway (that is, for the production of HA, keratan sulfate and sulfated GAGs) [21]. The authors also proposed that the chondroprotective effect of glucosamine results from the modulation of enzymes responsible for HA synthesis.…”
Section: Update On In Vitro Datamentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first study to suggest a negative effect of glucosamine. All prior studies, including those in articular cartilage, have demonstrated either no significant effect or beneficial effects on matrix homeostasis, including anti-catabolic effects, such as inhibition of matrix metalloproteinases or aggrecanases 14,15 , or improved anabolic activity 16 , In addition, our previous in vitro research on the effects of glucosamine on inflammation in the intervertebral disc paralleled evidence from articular cartilage, demonstrating anti-inflammatory activity 17,18 .…”
Section: Discussionmentioning
confidence: 78%
“…Аминосахар глюкозамин широко используется для облегчения симптомов ОА, возможно, потому что хондроциты используют этот сахар как структурный компонент для синтеза ГАГ в ВКМ [82]. Показано, что глюкозамин уменьшает скорость пролиферации, дифференцировки и минерализации фетальных и суставных хондроцитов [83,84] путем подавления катаболических ММП, аггреканаз, провоспалительных медиаторов, а также путем индукции синтеза проанаболической гиалуроновой кислоты in vitro [85][86][87].…”
Section: функции позитивных регуляторов Mtor в хондроцитахunclassified